Preparation method and application of nano lithium iron phosphate
Through laser liquid phase dissolution technology and subsequent spray drying and sintering steps, the problems of low yield, high cost and insufficient material activity in the preparation of nano-micro-scale lithium iron phosphate in the prior art are solved, and efficient preparation of nano-lithium iron phosphate has good dispersion and activity.
Patent Information
- Application Number
- CN202380012860.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-12-20
AI Technical Summary
The prior art has problems such as low yield, high cost, insufficient material particle size and insufficient activity when preparing lithium iron phosphate at nanoscale.
By adjusting the single pulse energy and the time of laser action, the ferric alcohol phosphate solvent was treated using laser liquid phase dissolution technology to prepare hydroxyl functional group-modified nanoferrous phosphate particles, and nanoferrous phosphate was obtained by spray drying and sintering steps.
The efficient refinement and dispersion of nano iron phosphate materials have been achieved, the product has no agglomeration, high dispersion, the particle size reaches the nanoscale, the shape is regular, and it has good activity and performance.
Smart Images

Figure CN117999242B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure belongs to the technical field of lithium-ion battery positive electrode materials, and particularly relates to a preparation method of nano-lithium iron phosphate and applications thereof. Background Art
[0002] As a positive electrode material for lithium-ion batteries, lithium iron phosphate (LIFP) boasts high specific capacity, excellent safety, long cycle life, and excellent thermal stability. Its widely available raw materials are inexpensive, making it a long-standing coexistence material with ternary materials. While LFP, a LFP cathode material for lithium-ion batteries, boasts advantages such as low cost, stable operating voltage, non-toxicity, environmental friendliness, stable structure, safety and reliability, excellent thermal stability, and long cycle life, it also suffers from disadvantages such as low ionic conductivity, poor low-temperature performance, and low tap density. Currently, LFP cathode materials are primarily synthesized via a high-temperature solid-phase reaction method, where a lithium source, iron source, phosphorus source, and doping or coating material are ground together and uniformly mixed, followed by sintering at high temperature. Other methods for synthesizing LFP include hydrothermal, co-precipitation, and microemulsion methods. While various methods exist for preparing LFP, the preparation of LFP using nano- and micro-scale iron phosphate as raw material is attracting significant attention. Currently, methods for preparing small-scale iron phosphates suffer from low yields, high costs, or insufficient particle size and activity. For example, mechanical grinding is used to prepare iron phosphate materials with small particle size. This method is usually time-consuming and energy-intensive, and the particles are prone to agglomeration, which prevents them from exposing more active sites. Summary of the Invention
[0003] The present disclosure aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present disclosure proposes a method for preparing nano-lithium iron phosphate and its application. The method mainly controls the product by adjusting the energy of a single pulse and the time of laser action. The laser acts on a continuously stirred alcohol-based solvent of iron phosphate, which effectively refines the iron phosphate while increasing the further reaction of the nano-iron phosphate particles with the surrounding liquid environment, thereby obtaining nano-iron phosphate particles modified with hydroxyl functional groups. The product has no agglomeration and high dispersibility.
[0004] According to one aspect of the present disclosure, a method for preparing nano-lithium iron phosphate is proposed, comprising the following steps:
[0005] S1: Dispersing ferric phosphate in an alcohol solvent and obtaining suspension A after ultrasonic treatment;
[0006] S2: treating the suspension A with a laser having a wavelength of 220-760 nm, a pulse width of 5-15 ns, a pulse frequency of 10-100 Hz, and a single pulse energy of 100-300 mJ. Stirring the suspension A during the laser treatment;
[0007] S3: adding a lithium source and a carbon source to the laser-treated suspension A, and mixing to obtain a suspension B;
[0008] S4: spray-drying the suspension B to obtain a dry powder, and sintering the dry powder under an inert atmosphere to obtain the nano-lithium iron phosphate.
[0009] In some embodiments of the present disclosure, in step S1, the particle size D50 of the iron phosphate is 1-20 μm.
[0010] In some embodiments of the present disclosure, in step S1, the alcohol solvent is at least one of isopropyl alcohol, ethanol, propanol, butanol, ethylene glycol or isobutyl alcohol.
[0011] In some embodiments of the present disclosure, in step S1, the frequency of the ultrasound is 40-60 KHz, and the time of the ultrasound is 10-30 min.
[0012] In some embodiments of the present disclosure, in step S1, the mass ratio of the ferric phosphate to the alcohol solvent is 1:(2-4).
[0013] In some embodiments of the present disclosure, in step S2, the laser treatment time is 0.5-2 hours.
[0014] In some embodiments of the present disclosure, in step S2, the stirring speed is 400-700 r / min.
[0015] In some embodiments of the present disclosure, in step S3, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium nitrate or lithium chloride.
[0016] In some embodiments of the present disclosure, in step S3, the molar ratio of Fe in the ferric phosphate to Li in the lithium source is 1:(1-1.05).
[0017] In some embodiments of the present disclosure, in step S3, the mass ratio of the ferric phosphate to the carbon source is 1:(0.14-0.17).
[0018] In some embodiments of the present disclosure, in step S3, the carbon source is at least one of glucose, citric acid, sucrose or ascorbic acid.
[0019] In some embodiments of the present disclosure, in step S4, the inlet air temperature of the spray drying is 180-200° C.; and the feed rate of the spray drying is 500-700 ml / h.
[0020] In some embodiments of the present disclosure, in step S4, the sintering temperature is 600-900°C.
[0021] In some embodiments of the present disclosure, in step S4, the sintering time is 8-14 hours.
[0022] In some embodiments of the present disclosure, in step S4, the particle size D50 of the nano-lithium iron phosphate is 8-40 nm.
[0023] The present disclosure also provides application of the preparation method in preparing lithium-ion batteries.
[0024] According to the embodiments of the present disclosure, there are at least the following beneficial effects:
[0025] 1. The present invention discloses a nano-iron phosphate material with uniform particles and good dispersion prepared by laser liquid phase ablation technology. When the iron phosphate in a stirred liquid is irradiated with a laser, the pulsed laser passes through the liquid and interacts with the material to generate a large amount of high-temperature plasma, forming a local environment of high temperature and high pressure. A laser-induced plasma plume is generated at the solid-liquid interface between the material and the liquid. Under the action of the high-energy laser ablation candle, the atoms or ions of the material have high kinetic energy. At the same time, due to the strong internal pressure inside the plasma plume, the molten solid phase material is ejected into the liquid phase environment. Finally, the plasma plume is quenched in the liquid. The nucleation and growth of the new phase occur in this process. The newly generated products diffuse outward into the liquid phase environment and quickly cool down to become the final nanomaterial. The quenching time of the plasma plume in the liquid is very short (approximately 100 nanoseconds), which makes the grain size of the grains grown during the plasma plume quenching process generally nanometer-scale. The prepared iron phosphate has good dispersion properties. At the same time, the sample particle size reaches nanometer level and the shape is regular.
[0026] 2. Select alcohol solvents as solvents for liquid-phase laser ablation, and under specific laser parameters, modify the surface of nanoparticles with functional groups through the action of laser. That is, by dissolving iron phosphate in a solvent containing -OH, nanoparticles with hydroxyl groups modified on the surface can be obtained. The groups are adsorbed on the surface of the particles, which can reduce the agglomeration of nanoparticles, improve the dispersion of the particles, and control the growth of grains during the subsequent sintering to prepare lithium iron phosphate. This preparation method can modify the target functional groups on nano-iron phosphate without adding surfactants, and there are no by-products. Compared with lithium iron phosphate materials prepared by mechanical ball milling and dissolution in aqueous solution, the lithium iron phosphate materials prepared by this method have small particle size and good dispersion, which is conducive to the insertion and removal of lithium ions and improves the utilization rate of active substances. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present disclosure is further described below with reference to the accompanying drawings and embodiments, wherein:
[0028] Figure 1This is a TEM image of lithium iron phosphate in Example 1 of the present disclosure;
[0029] Figure 2 This is a SEM image of lithium iron phosphate of Comparative Example 1 of the present disclosure;
[0030] Figure 3 This is a TEM image of lithium iron phosphate of comparative example 2 of the present disclosure. DETAILED DESCRIPTION
[0031] The following will clearly and completely describe the concept and technical effects of the present disclosure in conjunction with embodiments to fully understand the purpose, features and effects of the present disclosure.
[0032] Example 1
[0033] This embodiment prepares a nano-lithium iron phosphate, and the specific process is as follows:
[0034] (1) Weighing iron phosphate with a particle size D50 of 10 μm, dispersing it in isopropanol solvent, and performing ultrasonic dispersion at room temperature to obtain suspension A, wherein the mass ratio of iron phosphate to isopropanol is controlled to be 1:4, the frequency of ultrasonic dispersion is 53 kHz, and the dispersion time is 10 min;
[0035] (2) The suspension A was laser treated using a Nd:YAG pulsed laser with a laser wavelength of 532 nm, a pulse width of 10 ns, a pulse frequency of 10 Hz, a single pulse energy of 100 mJ, and an action time of 30 min. During the laser treatment, the suspension was stirred with a magnetic stirrer to keep the solution uniformly mixed at a stirring speed of 400 r / min.
[0036] (3) Add lithium carbonate to the laser-treated suspension A and stir and disperse it evenly, wherein the molar ratio of Fe in the iron phosphate to Li in the lithium carbonate is 1:1, and then add glucose, the mass of glucose being 0.14 times that of the iron phosphate, and stir and disperse it evenly to obtain suspension B.
[0037] (4) The suspension B was spray-dried at an inlet air temperature of 190°C and a feed rate of 600 ml / h to obtain a dry powder. The dry powder was then sintered in a nitrogen atmosphere, heated to 600°C at a rate of 3°C / min, and then maintained at this temperature for 8 hours. The material was cooled and discharged to obtain a LiFePO4 / C material with a particle size D50 of 40 nm.
[0038] Figure 1 This is the TEM image of lithium iron phosphate in this embodiment. Figure 1 It can be seen that the prepared LiFePO4 / C is in the form of dispersed nanoparticles with relatively uniform particle size.
[0039] Example 2
[0040] This embodiment prepares a nano-lithium iron phosphate, and the specific process is as follows:
[0041] (1) Iron phosphate with a particle size D50 of 10 μm was weighed and dispersed in isopropanol solvent, and ultrasonic dispersion was performed at room temperature to obtain suspension A, wherein the mass ratio of iron phosphate to isopropanol was controlled to be 1:2.5, the frequency of ultrasonic dispersion was 53 kHz, and the dispersion time was 15 min;
[0042] (2) The suspension A was laser treated using a Nd:YAG pulsed laser with a laser wavelength of 355 nm, a pulse width of 10 ns, a pulse frequency of 10 Hz, a single pulse energy of 150 mJ, and an action time of 1 h. During the laser treatment, the suspension was stirred with a magnetic stirrer to keep the solution uniformly mixed at a stirring speed of 500 r / min.
[0043] (3) Lithium carbonate was added to the laser-treated suspension A and stirred to disperse the mixture evenly, wherein the molar ratio of Fe in the iron phosphate to Li in the lithium carbonate was 1:1.02. Glucose was then added, with the amount of glucose being 0.15 times the mass of the iron phosphate, and stirred to disperse the mixture evenly, thereby obtaining suspension B.
[0044] (4) The suspension B was spray-dried at an inlet air temperature of 190°C and a feed rate of 600 ml / h to obtain a dry powder. The dry powder was then sintered in a nitrogen atmosphere, heated to 700°C at a rate of 3°C / min, and then kept at this temperature for 10 hours. The material was cooled and discharged to obtain a LiFePO4 / C material with a particle size D50 of 34 nm.
[0045] Example 3
[0046] This embodiment prepares a nano-lithium iron phosphate, and the specific process is as follows:
[0047] (1) Weighing iron phosphate with a particle size D50 of 20 μm, dispersing it in isopropanol solvent, and performing ultrasonic dispersion at room temperature to obtain suspension A, wherein the mass ratio of iron phosphate to isopropanol is controlled to be 1:3, the frequency of ultrasonic dispersion is 53 kHz, and the dispersion time is 20 min;
[0048] (2) The suspension A was laser treated using a Nd:YAG pulsed laser with a laser wavelength of 532 nm, a pulse width of 10 ns, a pulse frequency of 10 Hz, a single pulse energy of 200 mJ, and an action time of 1.5 h. During the laser treatment, the suspension was stirred with a magnetic stirrer to keep the solution uniformly mixed at a stirring speed of 600 r / min.
[0049] (3) Add lithium carbonate to the laser-treated suspension A and stir and disperse it evenly, wherein the molar ratio of Fe in the iron phosphate to Li in the lithium carbonate is 1:1.03, and then add glucose, the mass of glucose being 0.16 times that of the iron phosphate, and stir and disperse it evenly to obtain suspension B.
[0050] (4) The suspension B was spray-dried at an inlet air temperature of 190°C and a feed rate of 600 ml / h to obtain a dry powder. The dry powder was then sintered in a nitrogen atmosphere, heated to 800°C at a rate of 3°C / min, and then maintained at this temperature for 12 hours. The material was cooled and discharged to obtain a LiFePO4 / C material with a particle size D50 of 26 nm.
[0051] Example 4
[0052] This embodiment prepares a nano-lithium iron phosphate, and the specific process is as follows:
[0053] (1) Iron phosphate with a particle size D50 of 3 μm was weighed and dispersed in isopropanol solvent, and ultrasonic dispersion was performed at room temperature to obtain suspension A, wherein the mass ratio of iron phosphate to isopropanol was controlled to be 1:4, the frequency of ultrasonic dispersion was 53 kHz, and the dispersion time was 30 min;
[0054] (2) The suspension A was laser treated using a Nd:YAG pulsed laser with a wavelength of 760 nm, a pulse width of 10 ns, a pulse frequency of 10 Hz, a single pulse energy of 300 mJ, and an action time of 2 h. During the laser treatment, the suspension was stirred with a magnetic stirrer to keep the solution uniformly mixed at a stirring speed of 700 r / min.
[0055] (3) Lithium carbonate was added to the laser-treated suspension A and stirred to disperse the mixture evenly, wherein the molar ratio of Fe in the iron phosphate to Li in the lithium carbonate was 1:1.05. Glucose was then added, with the amount of glucose being 0.17 times the mass of the iron phosphate, and stirred to disperse the mixture evenly, thereby obtaining suspension B.
[0056] (4) The suspension B was spray-dried at an inlet air temperature of 190°C and a feed rate of 600 ml / h to obtain a dry powder. The dry powder was then sintered in a nitrogen atmosphere, heated to 900°C at a rate of 3°C / min, and then maintained at this temperature for 14 hours. The material was cooled and discharged to obtain a LiFePO4 / C material with a particle size D50 of 10 nm.
[0057] Comparative Example 1
[0058] This comparative example prepares a lithium iron phosphate. The difference from Example 1 is that the iron phosphate material with small particle size is prepared by ordinary mechanical grinding. The specific process is as follows:
[0059] (1) 20 g of ferric phosphate with a particle size D50 of 10 μm was weighed and added to the grinding chamber of a horizontal high-energy ball mill. Isopropyl alcohol was added as a solvent. The mass ratio of the material, balls, and isopropyl alcohol in the ball mill was 1:3:4. The mixture was ball milled at a speed of 1200 r / min for 18 h to obtain a mixed solution A.
[0060] (2) lithium carbonate was added to the mixed solution A and stirred to disperse uniformly, wherein the molar ratio of Fe in the ferric phosphate to Li in the lithium carbonate was 1:1, and glucose was added, wherein the mass of glucose was 0.14 times that of the ferric phosphate, and stirred to disperse uniformly to obtain a mixed solution B.
[0061] (3) The mixed solution B was spray dried with an inlet air temperature of 190°C and a feed rate of 600 ml / h to obtain a dry powder. The dry powder was then sintered in a nitrogen atmosphere, heated to 600°C at a rate of 3°C / min, and then kept at this temperature for 8 hours. The material was cooled and discharged to obtain a LiFePO4 / C material with a particle size D50 of 1 μm.
[0062] Comparative Example 2
[0063] This embodiment prepares a lithium iron phosphate. The difference from Example 3 is that isopropyl alcohol is replaced by deionized water. The specific process is as follows:
[0064] (1) Iron phosphate with a particle size D50 of 20 μm was weighed and dispersed in deionized water, and ultrasonic dispersion was performed at room temperature to obtain suspension A, wherein the mass ratio of iron phosphate to isopropanol was controlled to be 1:3, the frequency of ultrasonic dispersion was 53 kHz, and the dispersion time was 20 min;
[0065] (2) The suspension A was laser treated using a Nd:YAG pulsed laser with a laser wavelength of 532 nm, a pulse width of 10 ns, a pulse frequency of 10 Hz, a single pulse energy of 200 mJ, and an action time of 1.5 h. During the laser treatment, the suspension was stirred with a magnetic stirrer to keep the solution uniformly mixed at a stirring speed of 600 r / min.
[0066] (3) Add lithium carbonate to the laser-treated suspension A and stir and disperse it evenly, wherein the molar ratio of Fe in the iron phosphate to Li in the lithium carbonate is 1:1.03, and then add glucose, the mass of glucose being 0.16 times that of the iron phosphate, and stir and disperse it evenly to obtain suspension B.
[0067] (4) The suspension B was spray-dried at an inlet air temperature of 190°C and a feed rate of 600 ml / h to obtain a dry powder. The dry powder was then sintered in a nitrogen atmosphere, heated to 800°C at a rate of 3°C / min, and then maintained at this temperature for 12 hours. The material was cooled and discharged to obtain a LiFePO4 / C material with a particle size D50 of 27 nm.
[0068] Comparative Example 3
[0069] This embodiment prepares a lithium iron phosphate, which differs from embodiment 3 in that the laser parameters are different. The specific process is as follows:
[0070] (1) Iron phosphate with a particle size D50 of 20 μm was weighed and dispersed in isopropanol, and ultrasonic dispersion was performed at room temperature to obtain suspension A, wherein the mass ratio of iron phosphate to isopropanol was controlled to be 1:3, the frequency of ultrasonic dispersion was 53 kHz, and the dispersion time was 20 min;
[0071] (2) The suspension A was laser treated using a Nd:YAG pulsed laser with a laser wavelength of 1064 nm, a pulse width of 10 ns, a pulse frequency of 10 Hz, a single pulse energy of 60 mJ, and an action time of 1.5 h. During the laser treatment, the suspension was stirred with a magnetic stirrer to keep the solution uniformly mixed at a stirring speed of 600 r / min.
[0072] (3) Add lithium carbonate to the laser-treated suspension A and stir and disperse it evenly, wherein the molar ratio of Fe in the iron phosphate to Li in the lithium carbonate is 1:1.03, and then add glucose, the mass of glucose being 0.16 times that of the iron phosphate, and stir and disperse it evenly to obtain suspension B.
[0073] (4) The suspension B was spray-dried at an inlet air temperature of 190°C and a feed rate of 600 ml / h to obtain a dry powder. The dry powder was then sintered in a nitrogen atmosphere, heated to 800°C at a rate of 3°C / min, and then kept at this temperature for 12 hours. The material was cooled and discharged to obtain a LiFePO4 / C material with a particle size D50 of 53 nm.
[0074] Test example
[0075] The LiFePO4 / C material prepared in the above examples and comparative examples was selected as the positive electrode material. Acetylene black was selected as the conductive agent, and PVDF was selected as the binder. The positive electrode material, conductive agent, and binder were weighed in a ratio of 92:4:4. The organic solvent NMP was added, stirred, and coated onto aluminum foil to form a positive electrode sheet. A metallic lithium sheet was selected as the negative electrode. A button cell was fabricated in an argon-filled glove box. The electrochemical performance of the button cell was tested, and the results are shown in Table 1.
[0076] Table 1
[0077] 0.1C discharge capacity mAh / g 1C discharge capacity mAh / g 3C discharge capacity mAh / g Example 1 161.0 147.1 133.8 Example 2 161.7 148.0 134.6 Example 3 162.3 148.6 135.1 Example 4 161.2 147.8 134.0 Comparative Example 1 155.3 139.2 115.6 Comparative Example 2 159.8 145.6 130.8 Comparative Example 3 159.6 144.7 128.5
[0078] As can be seen from Table 1, the discharge capacities of Comparative Examples 1, 2, and 3 are all lower than those of Example 1. This is because Comparative Example 1 uses mechanical ball milling to crush and disperse the raw materials to prepare lithium iron phosphate. Figure 2It can be seen that the obtained fragmented lithium iron phosphate is seriously aggregated, unable to expose more active sites, resulting in reduced capacity. At the same time, mechanical ball milling consumes high energy and takes a long time to react. Comparative Example 2 uses deionized water as the liquid phase for laser ablation. Although nano-sized particles can also be prepared, Figure 3 Particle agglomeration is observed, and the dispersion is poorer than that of materials prepared using alcoholic solvents as the liquid phase. This suggests that the use of alcoholic solvents enables surface functional group modification of the iron phosphate during the laser process, preventing particle agglomeration and avoiding grain boundary fusion during the subsequent sintering process, resulting in well-dispersed nanoparticles. Comparative Example 3, using lower laser energy, not only lacks particle fineness but also fails to meet the conditions for hydroxyl surface modification. Particles agglomerate, reducing the material's capacity.
Claims
1. A method for preparing nano lithium iron phosphate, characterized in that: The following steps are involved: S1: Dispersing ferric phosphate in an alcohol solvent and obtaining a suspension A after ultrasonic treatment; S2: treating the suspension A with a laser, with a laser wavelength of 220-760 nm, a pulse width of 5-15 ns, a pulse frequency of 10-100 Hz, and a single pulse energy of 100-300 mJ, and stirring the suspension A during the laser treatment; S3: adding a lithium source and a carbon source to the laser-treated suspension A, and mixing to obtain a suspension B; S4: spray drying the suspension B to obtain a dry powder, and sintering the dry powder under an inert atmosphere to obtain the nano lithium iron phosphate; In step S1, the particle size D50 of the iron phosphate is 1-20 μm.
2. The preparation method according to claim 1, characterized in that: In step S1, the alcohol solvent is at least one of isopropanol, ethanol, propanol, butanol, ethylene glycol or isobutanol.
3. The preparation method according to claim 1, characterized in that: In step S1, the frequency of the ultrasound is 40-60 KHz, and the time of the ultrasound is 10-30 min.
4. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the iron phosphate to the alcohol solvent is 1:(2-4).
5. The preparation method according to claim 1, characterized in that: In step S2, the laser treatment time is 0.5-2h.
6. The preparation method according to claim 1, characterized in that: In step S2, the stirring speed is 400-700 r / min.
7. The preparation method according to claim 1, characterized in that: In step S3, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium nitrate or lithium chloride.
8. The preparation method according to claim 1, characterized in that: In step S3, the molar ratio of Fe in the iron phosphate to Li in the lithium source is 1:(1-1.05).
9. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the iron phosphate to the carbon source is 1:(0.14-0.17).
10. The preparation method according to claim 1, characterized in that: In step S3, the carbon source is at least one of glucose, citric acid, sucrose or ascorbic acid.
11. The preparation method according to claim 1, characterized in that: In step S4, the inlet air temperature of the spray drying is 180-200°C; the feed rate of the spray drying is 500-700 ml / h.
12. The preparation method according to claim 1, characterized in that: In step S4, the sintering temperature is 600-900°C.
13. The preparation method according to claim 1, characterized in that: In step S4, the sintering time is 8-14 hours.
14. The preparation method according to claim 1, characterized in that: In step S4, the particle size D50 of the nano lithium iron phosphate is 8-40 nm.
15. Use of the preparation method according to any one of claims 1 to 14 in the preparation of lithium ion batteries.
Citation Information
Patent Citations
Method for preparing single crystal TT-Nb2O5 nanorods
CN109292821A
Preparation of palladium-phosphorus-sulfur two-dimensional polycrystalline material and application thereof in electrochemical field
CN112742423A